2014
DOI: 10.15240/tul/001/2014-1-008
|View full text |Cite
|
Sign up to set email alerts
|

An econometric approach to factors affecting crop insurance in Romania

Abstract: AN ECONOMETRIC APPROACH TO FACTORS AFFECTING CROP INSURANCE IN ROMANIA

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
5
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 23 publications
1
5
0
Order By: Relevance
“…However, LIESIVAARA and MYYRÄ [2014] concluded that the demand for crop insurance products in Finland was higher among younger farmers. Similar results were also obtained by DRAGOS and MARE [2014], who observed a negative relationship between farmer's age and adoption of crop insurance in Romania. An assessment of the reasons for these mixed results could be the subject of future research.…”
Section: Resultssupporting
confidence: 87%
See 1 more Smart Citation

Journal of Water and Land Development

Namiotko,
Galnaitytė,
Kriščiukaitienė
et al. 2022
“…However, LIESIVAARA and MYYRÄ [2014] concluded that the demand for crop insurance products in Finland was higher among younger farmers. Similar results were also obtained by DRAGOS and MARE [2014], who observed a negative relationship between farmer's age and adoption of crop insurance in Romania. An assessment of the reasons for these mixed results could be the subject of future research.…”
Section: Resultssupporting
confidence: 87%
“…Also, SANTERAMO [2018] showed that successful experience in crop insurance was a catalyst for insurance participation. In addition to these reasons, DRAGOS and MARE [2014] also demonstrated that Romanian farmers did not participate in crop insurance due to lack of information from insurance companies.…”
Section: Introductionmentioning
confidence: 99%

Journal of Water and Land Development

Namiotko,
Galnaitytė,
Kriščiukaitienė
et al. 2022
“…(Rola, et al 2013). They have advocated the best way to overcome all the threats to agricultural sector and to improve rural welfare through agricultural or crop insurance (Dragos and Mare 2014). …”
Section: Introductionmentioning
confidence: 99%
“…Previous studies on agricultural insurance were mostly focused on the identification of the factors affecting agricultural insurance purchase decisions by farmers. The findings of these research generally revealed the effects of farmer characteristics such as educational background, age, level of income, size of enterprise, land use pattern and the effects of enterprise characteristics on agricultural insurance purchase decisions by farmers (Gül Yavuz, 2011;Kumar et al, 2011;Tümer, 2011;Dragos & Codruta, 2014). These findings constitute valuable inputs for determination of strategies to proliferate agricultural insurance programs.…”
Section: Resultsmentioning
confidence: 95%